EFL Preservice Teachers’ Intrinsic Motivation in Writing Essays in a Blended Learning Environment - Tri Wintolo Apoko (VELES Voices of English Language Education Society, 2023)
This research was aimed to examine EFL preservice teachers’ intrinsic motivation in writing essays in a blended learning environment. The method used in this research was a survey with quantitative description of opinions. The participants were 45 EFL preservice teachers of Universitas Muhammadiyah Prof. Dr. Hamka. The instrument was an online questionnaire to collect the data. The data were then analyzed with descriptive analysis to provide the mean and standard deviation. The results showed that EFL preservice teachers’ intrinsic motivations which include needs, interest, curiosity, and enjoyment were in high category. In other words, they have positive motivations in practicing to write essay in a blended learning environment. Thus, it was implied that it should have a boosting of maintaining EFL preservice teachers’ intrinsic motivation in writing essay in English for their better career and future.